(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Established as an experiment based on the decision of the head of our state on August 20, 2018, the Tashkent city "Ishga Marhamat" monocenter has been providing its services to the residents of all regions of our country. The decision of the head of our state dated August 11, 2020 "On additional measures aimed at attracting the poor and unemployed population to entrepreneurship, increasing their labor activity and vocational training, and ensuring employment of the population" became a normative basis for the establishment of monocenters in other regions. Even now, I cannot say that many people have a complete understanding of the activities of monocenters. The reason is that if someone comes to study for a profession, he comes to acquire skills in order to start another business. Monocenters provide short-term vocational training as well as other services. In particular, training and retraining for the unemployed population in technical, general construction, agricultural fields, digital technologies and other professions that are in high demand in the domestic and foreign labor market and professional development, teaching foreign languages, teaching the basics of entrepreneurship, development and popularization of working professions, knowledge, skills, qualifications and skills required for the implementation of professional activities, personal and professional knowledge, assessment of skills, abroad training citizens who want to work temporarily in professions and foreign languages, carrying out pre-adjustment measures with them. Young people are the main support of our nation. For this reason, necessary conditions are being created in our country for ensuring the rights and interests of young people, for their education, work, realizing their knowledge and abilities, and starting their career. In this regard, a comprehensive system is being created in our country, helping the realization of business initiatives, ideas and projects of young people, thereby ensuring their employment. According to a number of decrees and decisions of the President, preferential loans are of high importance for young people to engage in entrepreneurship.